Multimodality imaging employing positron emission tomography (PET) and multispectral optoacoustic tomography (MSOT) to investigate hypoxia in HPAF II tumours in vivo - Deng, Xiaozhou (2018)
Vasculature abnormalities and imbalance in oxygen homeostasis are associated with a pathological condition known as hypoxia. Hypoxia in tumours show a poor prognosis for cancer treatment outcome as it induces a favourable environment for tumour progression, metastases and chemotherapeutic resistance. Nevertheless, non-invasive imaging of tumour hypoxia could potentially be utilized to monitor disease progression and therapeutic treatment. The aim of the study is to investigate tumour hypoxia with multispectral optoacoustic tomography (MSOT) and positron emission tomography (PET) in vivo. Multimodality techniques were used to compare areas of compatibility and to assess tumour distribution of hypoxia in human pancreatic adenocarcinoma (HPAF-II) tumour xenografts. 8 female Cr Tac: NCr-Foxn1nu female nude mice were inoculated with HPAF II tumours because the tumour model possesses a heterogeneous vasculature with hypoxic regions. The anti-angiogenic cancer therapeutic, sunitinib malate, was chosen to modulate tumour hypoxia levels over time. 18F-Fluoromisonidazole (18F-FMISO) PET was used to delineate regions of tumour hypoxia and MSOT for quantitative measurement of saturated oxygen (sO2) in hypoxic tumours. Radiosynthesis of 18F-FMISO was done on SCINTOMICS GMP module and product could be obtained after 48 min with high radiochemical purity more than 99% and non-decay corrected radiochemical yield of 8-23%. Static acquisitions were performed at 110-120 min post injection and CT were used for tumour placement. We observed no effect of Sunitinib malate on mouse body weight, which indicates a lack of toxicity. The tumour growth had shown an approximate 50% inhibition by Day 7 post dosing of sunitinib malate. The tumour uptake of 18F-FMISO and MSOT sO2 data were compared in the same tumour, where the two imaging methodologies displayed complementary and inversely proportional information about the tumour oxygenation levels. Overall, our findings suggest 18F-FMISO PET and MSOT imaging methodologies demonstrated the potential for further application in imaging tumour hypoxia in vivo.